Mapping the imprints of stellar and active galactic nucleus feedback in the circumgalactic medium with X-ray microcalorimeters - Schellenberger, Gerrit; Bogdán, Ákos; ZuHone, John A.; Oppenheimer, Benjamin D.; Truong, Nhut; Khabibullin, Ildar; Jennings, Fred; Pillepich, Annalisa; Burchett, Joseph; Carr, Christopher; Chakraborty, Priyanka; Crain, Robert; et al. (The astrophysical journal, 2024)
The Astro2020 Decadal Survey has identified the mapping of the circumgalactic medium (CGM; the gaseous plasma around galaxies) as a key objective. We explore the prospects for characterizing the CGM in and around nearby galaxy halos with a future large-grasp X-ray microcalorimeter. We create realistic mock observations from hydrodynamical simulations (EAGLE, IllustrisTNG, and Simba) that demonstrate a wide range of potential measurements, which will address the open questions in galaxy formation and evolution. By including all background and foreground components in our mock observations, we show why it is impossible to perform these measurements with current instruments, such as X-ray CCDs, and why only microcalorimeters will allow us to distinguish the faint CGM emission from the bright Milky Way (MW) foreground emission lines. We find that individual halos of MW mass can, on average and depending on star formation rate, be traced out to large radii, around R 500, and for larger galaxies even out to R 200, using prominent emission lines, such as O vii, or O viii. Furthermore, we show that emission-line ratios for individual halos can reveal the radial temperature structure. Substructure measurements show that it will be possible to relate azimuthal variations to the feedback mode of the galaxy. We demonstrate the ability to construct temperature, velocity, and abundance ratio maps from spectral fitting for individual galaxy halos, which reveal rotation features, active galactic nucleus outbursts, and enrichment.
Gesehen am 26.02.2025